1983
DOI: 10.1073/pnas.80.21.6606
|View full text |Cite
|
Sign up to set email alerts
|

Azacytidine-induced tumorigenesis of CHEF/18 cells: correlated DNA methylation and chromosome changes.

Abstract: 5-Azacytidine (azaC), a drug that induces decreased methylation of DNA in mammalian cells, was shown previously to induce differentiation of mesenchymal cell types in CHEF/18 cells (Chinese hamster embryo fibroblasts). This paper describes the effectiveness of azaC in inducing tumorigenicity in CHEF/18 cells, previously shown to be nontumorigenic stable diploids. A short exposure of growing cells to 3 ,LM azaC induced tumor-forming ability in CHEF/18 stem cells. Pre-adipocyte clones and subelones derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 25 publications
(22 reference statements)
3
28
0
Order By: Relevance
“…However, several observations support the notion that the hypomethylating effect of 5-AC is responsible for the induction of cell transformation: the results of Walker and Nettesheim (1986) show that the analog 6-azacytidine, which does not cause DNA hypomethylation, did not transform rat tracheal epithelial cells. Hsiao et al (1985) and Harrison et al (1983) have shown that 5-AC can neoplastically transform established cell Iines, suggesting that changes in methylation occurring during later stages of transformation can result in the conversion of immortal cells to neoplastic cells. Further characterization of the process of malignant progression induced by 5-AC and related compounds, and molecular analysis of immortalized and neoplastic cells seem necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several observations support the notion that the hypomethylating effect of 5-AC is responsible for the induction of cell transformation: the results of Walker and Nettesheim (1986) show that the analog 6-azacytidine, which does not cause DNA hypomethylation, did not transform rat tracheal epithelial cells. Hsiao et al (1985) and Harrison et al (1983) have shown that 5-AC can neoplastically transform established cell Iines, suggesting that changes in methylation occurring during later stages of transformation can result in the conversion of immortal cells to neoplastic cells. Further characterization of the process of malignant progression induced by 5-AC and related compounds, and molecular analysis of immortalized and neoplastic cells seem necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A block in the G 2 phase of the cell cycle was also reported by Zatsepina et al (1989) in pig kidney cells. 5-AC transformed cultures of 10T1 /2 and M2 mouse fibroblasts (Benedict et al, 1977;Harrison et al, 1983), primary rat tracheal epithelial cells (Walker and Nettesheim, 1986) and Balbjc-3T3 cells (Lubet et al, 1990).…”
mentioning
confidence: 99%
“…The results of 5-azacytidine action are expected to be complex. On the one hand, 5-azacytidine is capable of enhancing or inducing the metastatic capacity of various tumour cell lines (Olsson & Forchammer, 1984;Trainer et al, 1985;Ormerod et al, 1986), activating silent retroviral genomes (Jaenisch et al, 1985), enhancing the induction by various carcinogens of gamma-glutamyltransferase positive liver foci (Denda et al, 1985), of altering cellular DNA which is incapable of inducing transformation (Venolia et al, 1982), and of inducing tumorigenesis in various cells in culture (Venolia et al, 1982;Harrison et al, 1983;Benedict et al, 1977;Marquardt & Marquardt, 1977), even though it does not appear to be a significant mutagen in mammalian cells (Landolph & Jones, 1982;Frost et al, 1984;Momparler et al, 1984;Delers et al, 1984;Bouck et al, 1984;Jones, 1984). On the other hand, 5-azacytidine has been shown to induce differentiation in both non-transformed as well as in neoplastic cells in culture (Constantinides et al, 1977(Constantinides et al, , 1978Jones & Taylor, 1980;Walker et al, 1984;Creusot et al, 1982;Darmon et al, 1984;Pinto et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…De novo methylation has been observed principally with integrated viral genomes (6,26) and has been attributed to site-specific methyltransferase activity (6) or to the appearance of new chromatin conformations that invite methylation by a nonspecific enzyme (2). Methylation losses have been reported during development (26), in terminal differentiation (6), and in tumorigenesis (9,13) and have been attributed to dilution or inactivation of a preexisting enzyme (6) or to the presence of a demethylating enzyme (10). The dynamics of DNA methylation, how changes occur in methylation patterns at specific sites, remains largely unknown.…”
mentioning
confidence: 99%